"Cross-editing": Comparing News Output Through Journalists' Re-working of Their Rivals' Scripts. (26th April 2021) - Marsh, Vivien
ABSTRACT: Newsdesk journalists make thousands of editorial decisions every day without recourse to style guides. They can do this because they have internalised the aims and values of their news organisations: they know what counts as a "good story" for their output. This paper describes a pioneering micro-level comparative method of studying journalistic values in which, unlike in other comparative studies, the journalists themselves perform the initial analysis. In essence, newsdesk editors from two news organisations swap scripts. They evaluate, edit and mark up their rivals' texts as if they were being asked to use them in their own output. What would they alter, insert or leave out? Would they reject a story completely? This "cross-edit" and the editors' additional observations represent unmediated analysis from inside the news editing process, allowing researchers to draw comparative conclusions grounded principally in discourse analysis. To pilot the method, a number of journalists from the BBC and China's official English-language news provider, CCTV-News (now CGTN), cross-edited selected news scripts published by their rivals. The technique shed new light on news routines, lexical choices, omissions and unexpected consonances in news values. It was then refined to provide a framework for future, wider use.